Surface expression of protein A on magnetosomes and capture of pathogenic bacteria by magnetosome/antibody complexes - Xu, Jun; Hu, Junying; Liu, Lingzi; Li, Li; Wang, Xu; Zhang, Huiyuan; Jiang, Wei; Tian, Jiesheng; Li, Ying; Li, Jilun (Frontiers in Microbiology, 2014)
Magnetosomes are membrane-enclosed magnetite nanocrystals synthesized by magnetotactic bacteria (MTB). They display chemical purity, narrow size ranges, and species-specific crystal morphologies. Specific transmembrane proteins are sorted to the magnetosome membrane (MM). MamC is the most abundant MM protein of Magnetospirillum gryphiswaldense strain MSR-1. MamF is the second most abundant MM protein of MSR-1 and forms stable oligomers. We expressed staphylococcal protein A (SPA), an immunoglobulin-binding protein from the cell wall of Staphylococcus aureus, on MSR-1 magnetosomes by fusion with MamC or MamF. The resulting recombinant magnetosomes were capable of self-assembly with the Fc region of mammalian antibodies (Abs) and were therefore useful for functionalization of magnetosomes. Recombinant plasmids pBBR-mamC-spa and pBBR-mamF-spa were constructed by fusing spa (the gene that encodes SPA) with mamC and mamF, respectively. Recombinant magnetosomes with surface expression of SPA were generated by introduction of these fusion genes into wild-type MSR-1 or a mamF mutant strain. Studies with a Zeta Potential Analyzer showed that the recombinant magnetosomes had hydrated radii significantly smaller than those of WT magnetosomes and zeta potentials less than -30 mV, indicating that the magnetosome colloids were relatively stable. Observed conjugation efficiencies were as high as 71.24 µg Ab per mg recombinant magnetosomes, and the conjugated Abs retained most of their activity. Numbers of Vibrio parahaemolyticus (a common pathogenic bacterium in seafood) captured by recombinant magnetosome/ Ab complexes were measured by real-time fluorescence-based quantitative PCR. One mg of complex was capable of capturing as many as 1.74×107 Vibrio cells. The surface expression system described here will be useful for design of functionalized magnetosomes from MSR-1 and other MTB.